2008
DOI: 10.1113/jphysiol.2008.158121
|View full text |Cite
|
Sign up to set email alerts
|

Sleep fragmentation impairs ventilatory long‐term facilitation via adenosine A1 receptors

Abstract: Sleep fragmentation (SF), a primary feature of obstructive sleep apnoea (OSA), impairs hippocampal long-term potentiation and causes cognitive/attention deficits. However, its influence upon respiratory control has hardly been studied. This study examined the effect of SF on ventilatory long-term facilitation (LTF, a persistent augmentation of respiratory activity after episodic hypoxia) and the hypoxic ventilatory response (HVR), and investigated the role of adenosine A1 receptors in these SF effects in consc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 55 publications
(87 reference statements)
3
27
2
Order By: Relevance
“…The 24 h SF was achieved by periodic, forced locomotion (30 s rotation followed by 90 s stop) at a speed of ~1.5 rotation/min for a 24 h period (started at 08.00 h and ended at 08.00 h on the following morning), as previously described (McGuire et al, 2008b). This SF protocol successfully produced up to ~30 sleep interruptions per hour (McGuire et al, 2008b), a frequency often observed in OSA patients (Wiegand and Zwillich, 1994). Before SF treatment, rats were given 2 days to acclimatize to the drum (~30 min periodic rotation in each day).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 24 h SF was achieved by periodic, forced locomotion (30 s rotation followed by 90 s stop) at a speed of ~1.5 rotation/min for a 24 h period (started at 08.00 h and ended at 08.00 h on the following morning), as previously described (McGuire et al, 2008b). This SF protocol successfully produced up to ~30 sleep interruptions per hour (McGuire et al, 2008b), a frequency often observed in OSA patients (Wiegand and Zwillich, 1994). Before SF treatment, rats were given 2 days to acclimatize to the drum (~30 min periodic rotation in each day).…”
Section: Methodsmentioning
confidence: 99%
“…The 24 h LC treatment was also achieved by periodic, forced locomotion in the same drums as previously described (McGuire et al, 2008b). Both rotation and stop times were lengthened (15 min rotation/45 min stop) to allow for deep and consolidated sleep during the 45 min stop periods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been postulated that repeated hypocapnia between OSA events might inhibit LTF expression in OSA patients (12). However, it should be noted that hypercapnia will always occur concomitant with hypoxia during OSA events, and LTF, if elicited, is quite resilient to various disturbances in rats (13), although recent findings suggest it may be impacted by sleep deprivation/sleep fragmentation (14).…”
mentioning
confidence: 98%
“…Forty-eight-hour TSD (from 09: 00 to 09: 00) was achieved by slowly rotating the wheels at a constant speed (0.3 m/min) [16][17][18] . Three controls were used in the experiment.…”
Section: Total Sleep Deprivationmentioning
confidence: 99%